Integration in reading literacy: a systematic review of pedagogical, professional, and engagement approaches - Md Zahril Nizam Md Yusoff; Wan Nur Aida Sakinah Wan Jusoh; Norfaizah Abdul Jobar; Noor Zuhidayah Muhd Zulkipli; Muhamad Fadzllah Zaini; Tajul Shuhaizam Said (International Journal of Evaluation and Research in Education (IJERE), 2026)
This systematic literature review (SLR) following preferred reporting items for systematic reviews and meta-analyses (PRISMA) 2020 who explores integrated approaches to reading literacy across pedagogical integration, teacher development, and student engagement. From 1,108 retrieved articles, 59 article high-quality studies were selected for in-depth synthesis. Based on all studies published between 2020 and 2024, the findings reveal that multimodal instruction, inclusive pedagogy, and proposes a cohesive framework linking instructional innovation, teacher agency, and learner experience, offering actionable insights for educators and policymakers. The analysis identified three key thematic drivers of literacy improvement. First, integrated pedagogical practices such as multimodal, bilingual, and play-based instruction enhance literacy by making learning more inclusive, interactive, and context-responsive. Second, teacher professional development through targeted training in visual literacy, inclusive pedagogy, and digital tools strengthens instructional quality and prepares educators for evolving literacy demands. These approaches reflect current trends in instructional innovation and professional capacity building. Third, student engagement is significantly elevated through identity-driven learning, project-based tasks, and emotionally supportive environments that foster confidence, motivation, and deeper literacy outcomes. Together, these themes forms a new integration model that links teaching practices, teacher agency, and student experience into a cohesive literacy framework. The findings offer practical, evidence-based insights for policymakers, curriculum designers, and practitioners aiming to improve reading literacy across diverse settings.